AGR2 oncoprotein inhibits p38 MAPK and p53 activation through a DUSP10-mediated regulatory pathway - Hrstka, Roman; Bouchalova, Pavla; Michalova, Eva; Matoulkova, Eva; Muller, Petr; Coates, Philip J; Vojtesek, Borivoj (Molecular oncology, 2016)
The tumor suppressor p53 plays a key role in malignant transformation and tumor development. However, the frequency of p53 mutations within individual types of cancer is different, suggesting the existence of other mechanisms attenuating p53 tumor suppressor activity. Changes in upstream regulators of p53 such as MDM2 amplification and overexpression, expression of viral oncoproteins, estrogen receptor signaling, or changes in p53 transcriptional target genes were previously described in wild-type p53 tumors. We identified a novel pathway responsible for attenuation of p53 activity in human cancers. We demonstrate that AGR2, which is overexpressed in a variety of human cancers and provides a poor prognosis, up-regulates DUSP10 which subsequently inhibits p38 MAPK and prevents p53 activation by phosphorylation. Analysis of human breast cancers reveals that AGR2 specifically provides a poor prognosis in ER+ breast cancers with wild-type p53 but not ER- or mutant p53 breast cancers, and analysis of independent data sets show that DUSP10 levels also have prognostic significance in this specific sub-group of patients. These data not only reveal a novel pro-oncogenic signaling pathway mediating resistance to DNA damaging agents in human tumors, but also has implications for designing alternative strategies for modulation of wild-type p53 activity in cancer therapy.
Keywords: nádorový supresorový protein p53; senioři; Breast; Oncogene Proteins; nádorové buněčné linie; signální transdukce; Breast Neoplasms; prsy; mukoproteiny; Mitogen-Activated Protein Kinase Phosphatases; DUSP10; proteiny; fosfatasy MAP kinas; Middle Aged; onkogenní proteiny; Signal Transduction; Tumor Suppressor Protein p53; Adult; Cell Line, Tumor; fosfatasy s dvojí specifitou; Antineoplastic Agents; Breast cancer; chemorezistence; Neoplasms; p53; Enzyme Activation; ženské pohlaví; protinádorové látky; Humans; Drug Resistance, Neoplasm; nádory; Dual-Specificity Phosphatases; mitogenem aktivované proteinkinasy p38; lidé středního věku; aktivace enzymů; nádory prsu; p38 MAPK; Drug resistance; p38 Mitogen-Activated Protein Kinases; dospělí; Mucoproteins; AGR2; Female; Aged; Proteins; lidé